Glucose and glutamine metabolism in relation to mutational status in NSCLC histological subtypes. Issue 12 (30th October 2019) - Meijer, Tineke W.H.; Looijen‐Salamon, Monika G.; Lok, Jasper; van den Heuvel, Michel; Tops, Bastiaan; Kaanders, Johannes H.A.M.; Span, Paul N.; Bussink, Johan
Abstract: Background: Both hypoxia and oncogenic mutations rewire tumor metabolism. In this study, glucose and glutamine metabolism‐related markers were examined in stage I ‐ resectable stage IIIA non‐small cell lung cancer (NSCLC). Furthermore, expression of metabolism‐related markers was correlated with mutational status to examine mutations associated with rewired tumor metabolism. Methods: Mutation analysis was performed for 97 tumors. Glucose and glutamine metabolism‐related marker expression was measured by immunofluorescent staining (protein) and qPCR (mRNA) ( n = 81). Results: Glutamine metabolism‐related markers were significantly higher in adeno‐ than squamous cell NSCLCs. Glucose transporter 1 (GLUT1) protein expression was higher in solid compared to lepidic adenocarcinomas ( P < 0.01). In adenocarcinomas, mRNA expression of glutamine transporter SLC1A5 correlated with tumor size (r(p) = 0.41, P = 0.005). Furthermore, SLC1A5 protein expression was significantly higher in adenocarcinomas with worse pTNM stage (r(s) = 0.39, P = 0.009). EGFR ‐mutated tumors showed lower GLUT1 protein ( P = 0.017), higher glutaminase 2 (GLS2) protein ( P = 0.025) and higher GLS2 mRNA expression ( P = 0.004), compared to EGFR wild‐type tumors. GLS mRNA expression was higher in KRAS ‐mutated tumors ( P = 0.019). TP53 ‐mutated tumors showed higher GLUT1 expression ( P = 0.009). Conclusions: NSCLC is a heterogeneous disease, with differences in mutational status and metabolism‐related marker expression between adeno‐ and squamous cell NSCLCs, and also within adenocarcinoma subtypes. GLUT1 and SLC1A5 expression correlate with aggressive tumor behavior in adenocarcinomas but not in squamous cell NSCLCs. Therefore, these markers could steer treatment modification for subgroups of adenocarcinoma patients. TP53, EGFR and KRAS mutations are associated with expression of glucose and glutamine metabolism‐related markers in NSCLC.